2017
DOI: 10.1038/nchembio.2330
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic discovery of polybrominated diphenyl ether biosynthesis by marine sponges

Abstract: Naturally produced polybrominated diphenyl ethers (PBDEs) pervade the marine environment and structurally resemble toxic man-made brominated flame retardants. PBDEs bioaccumulate in marine animals and are likely transferred to the human food chain. However, the biogenic basis for PBDE production in one of their most prolific sources, marine sponges of the order Dysideidae, remains unidentified. Here, we report the discovery of PBDE biosynthetic gene clusters within sponge microbiome-associated cyanobacterial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(191 citation statements)
references
References 61 publications
3
188
0
Order By: Relevance
“…For example, marine bacteria express enzymes that synthesize OH-PBDEs and their derivatives. 1,1922 Like their anthropogenic counterparts, marine HOCs accumulate in marine mammals, Antarctic air, seabird eggs, and human breast milk, possibly adding to adverse health risks. 2327 Recently, the biosynthetic pathways for a number of brominated pyrroles, bipyrroles and phenols have been also elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, marine bacteria express enzymes that synthesize OH-PBDEs and their derivatives. 1,1922 Like their anthropogenic counterparts, marine HOCs accumulate in marine mammals, Antarctic air, seabird eggs, and human breast milk, possibly adding to adverse health risks. 2327 Recently, the biosynthetic pathways for a number of brominated pyrroles, bipyrroles and phenols have been also elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…2327 Recently, the biosynthetic pathways for a number of brominated pyrroles, bipyrroles and phenols have been also elucidated. 1,19,21,28 Tetrabromopyrrole ( 31 ) isolated from Pseudoalteromonas bacteria has been shown to elicit specific development cues to coral larvae necessary for metamorphosis and benthic attachment of Orbicella franksi and Acropora palmata onto crustose coralline algae. 29,30 Remarkably, high levels of several halopyrroles, including tetrabromopyrrole ( 31 ), are produced as disinfection byproducts (DBPs) during treatment of drinking water, agricultural irrigation water and saline wastewater, and are considered as emerging pollutants because of their cytotoxicity, genotoxicity, carcinogenicity and developmental toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one current report revealed that the cyanobacterium, Hormoscilla spongeliae (formerly Oscillatoria spongeliae), is the real producer of the polybrominated diphenyl ethers in Dysideidae sponges through the metagenome mining approach of the sponge-microbiome. [16] It is also proposed that cyanobacteria, Moorea producens, Pleurocapsa sp., and Rivularia sp. may produce these secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…However, the production source of these PDBEs within these sponges was previously unknown. A study carried out by Agarwal et al [156] has now reported the discovery of biosynthetic gene clusters through the metagenome mining approach of the sponge-microbiome and identified association of these biosynthetic gene clusters within a sponge-associated cyanobacterial endosymbiont. Thus, investigating bioactive marine sponges through metagenomics may reveal the biosynthetic gene clusters which can then be incorporated into microorganisms that may be easily be grown within the laboratory [156].…”
Section: Production Of Natural Products By Sponge Symbiontsmentioning
confidence: 99%
“…'OSMAC' is the term for 'one strain many compounds', which is the ability of a single strain to produce different compounds when grown under differing conditions [156]. The culturing of a marine fungus, Spicaria elegans, which was grown under 10 different culture conditions was shown to produce a range of new compounds including the novel spicochalasin A, five new aspochalasins M-Q, and two known aspochalasins [234].…”
Section: Altering Growth Conditions and Co-cultivation Of Microorganismsmentioning
confidence: 99%